The Genomic Landscape and Evolutionary Resolution of Antagonistic Pleiotropy in Yeast - Qian, Wenfeng; Ma, Di; Xiao, Che; Wang, Zhi; Zhang, Jianzhi (Cell reports (Cambridge), 2012)
Antagonistic pleiotropy (AP), or genetic tradeoff, is an important concept that is frequently invoked in theories of aging, cancer, genetic disease, and other common phenomena. However, the prevalence of AP, which genes are subject to AP, and to what extent and how AP may be resolved remain unclear. By measuring the fitness difference between the wild-type and null alleles of ∼5,000 nonessential genes in yeast, we found that in any given environment, yeast expresses hundreds of genes that harm rather than benefit the organism, demonstrating widespread AP. Nonetheless, under sufficient selection, AP is often resolvable through regulatory evolution, primarily by trans-acting changes, although in one case we also detected a cis-acting change and localized its causal mutation. However, AP is resolved more slowly in smaller populations, predicting more unresolved AP in multicellular organisms than in yeast. These findings provide an empirical foundation for AP-dependent theories and have broad biomedical and evolutionary implications. [Display omitted] ► Under any conditions, yeast expresses many genes that are harmful to the cell ► Such problems can often be resolved by regulatory evolution under selection ► Such regulatory evolution tends to occur via trans-acting genetic changes ► Antagonistic pleiotropy is predicted to be more abundant in multicellular organisms Antagonistic pleiotropy (AP) refers to the situation in which the relative advantage of two alleles of a gene is reversed in different components of fitness, such as different sexes or external environments. AP is frequently invoked in theories of aging, cancer, genetic disease, and adaptation. However, the prevalence of AP, which genes are subject to AP, and to what extent and how AP may be resolved remain unclear. Zhang and colleagues address these questions by a combination of genomics, genetics, and modeling in yeast.